Isoseismal map of the 2015 Nepal earthquake and its relationships with ground-motion parameters, distance and magnitude. (1st January 2017) - Prajapati, Sanjay K.; Dadhich, Harendra K.; Chopra, Sumer
Highlights: Preparation of isoseismal map of Gorkha, Nepal Earthquake. Derived the empirical relation between Ground motion parameter and Modified Mercalli Intensity. Derived a relationship between magnitude, intensity and ground motion parameter using recent Nepal and historical earthquake. Present result can be used for generating shake map for the Himalaya region and other engineering applications. Abstract: A devastating earthquake of Mw 7.8 struck central Nepal on 25th April, 2015 (6:11:25 UT) which resulted in more than ∼9000 deaths, and destroyed millions of houses. Standing buildings, roads and electrical installations worth 25–30 billions of dollars are reduced to rubbles. The earthquake was widely felt in the northern parts of India and moderate damage have been observed in the northern part of UP and Bihar region of India. Maximum intensity IX, according to the USGS report, was observed in the meizoseismal zone, surrounding the Kathmandu region. In the present study, we have compiled available information from the print, electronic media and various reports of damages and other effects caused by the event, and interpreted them to obtain Modified Mercalli Intensities (MMI) at over 175 locations spread over Nepal and surrounding Indian and Tibet region. We have also obtained a number of strong motion recordings from India and Nepal seismic network and developed an empirical relationship between the MMI and peak ground acceleration (PGA), peak ground velocity (PGV). We have used least square regression technique to derive the empirical relation between the MMI and ground motion parameters and compared them with the empirical relationships available for other regions of the world. Further, seismic intensity information available for historical earthquakes, which have occurred in the Nepal Himalaya along with the present intensity data has been utilized for developing an attenuation relationship for the studied region using two step regression analyses. The derived attenuation relationship is useful for assessing damage of a potential future large earthquake (earthquake scenario-based planning purposes) in the region.